Molecular characterisation of squamous cell carcinoma antigen recognised by T-cells 3, an adaptor protein of ubiquitin specific protease 15 - Grazette, Affif (2016)
The deubiquitinating enzyme USP15, a member of the USP family, reverses the process of ubiquitination thereby altering the fate of a plethora of substrates. As such, USP15 has been implicated in a numerous important cellular pathways including cell cycle progression, transcriptional modification and DNA damage repair. The spliceosomal subunit recycling protein SART3 has been shown to bind to USP15 enhancing its deubiquitination of histone H2B thereby providing histone dimers for reassembly during subsequent rounds of transcription and splicing. Furthermore SART3 has also been shown to bind to USP4, a close homologue of USP15. In addition to this histone chaperone activity, SART3 primarily functions by mediating the re-annealing of the U4 and U6 snRNPs to facilitate consequent rounds of splicing in addition to its implication in several disease states including numerous cancer types and HIV through interactions with various cellular proteins. In this thesis ITC, ESI-MS, analytical size exclusion, X-ray crystallography, SAXS and pull-down assays are used to characterise the interaction between USP15 and SART3, solve the structure of the N-terminus of SART3 and identify novel binding partners of the USP15-SART3 complex. The structure of SART3’s N-terminus (residues 96-574) has been solved to 3.04Å, revealing that it is a homodimer comprised of a series of anti-parallel α-helices that form a shape reminiscent of a bowtie. This dimeric arrangement is retained in solution and can bind two molecules of USP15DU. The DU-finger of USP15 plays a pivotal role in co-ordinating the binding interaction with SART3, as small changes to this region can affect the nanomolar affinity interaction between USP15 and SART3. In addition the USP15-SART3 complex appears to interact with several cellular proteins which could have significant impact in several disease states.